Novel Umami Ingredients: Umami Peptides and Their Taste - Zhang, Yin; Venkitasamy, Chandrasekar; Pan, Zhongli; Liu, Wenlong; Zhao, Liming (Journal of food science, 2017)
Umami substances are very important for food seasoning and healthy eating. In addition to monosodium glutamate and some nucleotides, recent investigations have revealed that several peptides also exhibit umami taste. In recent years, 52 peptides have been reported to show umami taste, including 24 dipeptides, 16 tripeptides, 5 octapeptides, 2 pentapeptides, 2 hexapeptides, 1 tetrapeptide, 1 heptapeptide, and 1 undecapeptide. Twenty of these peptides have been examined for the present of umami taste. In this review, we have listed these umami peptides based on their category, source, taste, and threshold concentration. The evidence for peptides showing umami taste, the umami taste receptors on the human tongue, and the peptides whose umami taste is controversial are also discussed.